Paraganglioma of common bile duct: a case report - Muhammad Ammar Pirzada; Muhammad Rizwan Khan; Saleema Begum; Khurram Minhas (Journal of the Pakistan Medical Association, 2022)
Paragangliomas are rare tumours derived from the neural crest cells. Most common site for these tumours is the adrenal medulla, where they are called as pheochromocytomas. Biliary system is an extremely uncommon site for extra-adrenal paraganglioma. We report the case of a 55 year old female who presented with one-month history of jaundice and right upper quadrant discomfort. Imaging showed a well-defined rounded mass at porta hepatis with arterial enhancement causing compression over the proximal common bile duct, resulting in moderate intrahepatic biliary dilatation. The patient underwent radical excision of common bile duct and roux-en-y hepaticojejunostomy. Final histopathology confirmed paraganglioma. Approximately 10% of the patients may present with extra-adrenal disease, but biliary paraganglioma are extremely rare. Only few cases have been reported in literature and the management usually involves the surgical excision. ---Continue